Pelatihan Teknik Caesar Cipher Terhadap Keamanan Informasi - Azhar, Asbon Hendra; Destari, Ratih Adinda; Negoro, Wahyu Sapta; Ardansyah, A (LPPM STIKOM Tunas Bangsa, 2024)
The concept of cryptography has been used since ancient times by Julius Caesar and continues to develop today. Based on the era, cryptography is divided into two parts, namely classical cryptography and modern cryptography. The similarity between the two is that they both use mathematical concepts in the technique of creating and breaking a message. But in classical cryptography, the mathematical concepts used are still very simple, such as substitution, permutation and transpose. Meanwhile, in modern cryptography the mathematical concepts used are no longer simple, such as polynomials, prime numbers, groups, rings and fields. The advantage of classical cryptography is that it is easy to encrypt messages, but some encryption techniques also have a fatal weakness, namely that they are very easy to crack. An example of classic cryptography that is very easy to create and solve is the Caesar Cipher which only has 26 possible keys. Caesar Cipher is included in the Substitution Cipher encryption, where a random code or script is obtained by replacing each character in the original text.